Dalits in India Search for a common destiny - Thorat, Sukhadeo (Sage, 2009)
This book explores the status of dalits in the country by presenting all-India and state-level analyses of various human development and related social and economic indicators. It provides a comprehensive understanding of the processes and dynamics that exclude them from mainstream development and are causative of their relative peripheral position.